Flash Remoting: The Definitive Guide - Muck, Tom (O'Reilly, 2011)
Flash Remoting MX lets developers easily integrate rich Macromedia Flash content with applications that are built using ColdFusion, ASP.NET, Java, PHP, or SOAP-based web services. The result is complex client/server applications that more closely resemble desktop applications than traditional web pages. Build applications that connect to a database, file system, or other server-side technologies. Developers who are looking to create Rich Internet Applications with the Flash will find Flash Remoting: The Definitive Guide indispensable.